National Education Paradigm Ahmad Tafsir Perspective - Aslamiyah, Mauldia; Fauzi, Amin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
This article examines Ahmad Tafsir's views on the national education paradigm aimed at enlightening the nation's life and building Indonesia fully integrated with religious values. The type of research used is library research, and the data sources in this study are taken from relevant books and journals. From the review of books and journals, an explanation according to Ahmad Tafsir can be obtained that education in Indonesia must be based on the paradigm of faith, where faith-based education shapes character and enhances the nation's morals, as well as emphasizes the importance of integrating moral and scientific values into the education system. Faith becomes the core of the curriculum based on God the Almighty, which is the national education goal to shape students' character and noble morals in the educational process. According to Ahmad Tafsir, the education curriculum has three main pillars: moral, knowledge, and artistic skills. By prioritizing morality as the core of education, this paradigm also drives change and meets the needs of society in the face of global challenges, ensuring adherence to religious values and rooting all activities in faith. Thus, faith is the core of Pancasila, faith is the core of the 1945 Constitution, and faith is the core of national education.